Determinação da cinética de reação e condições operacionais da pirólise em leito fixo da casca de café - Lima, Mariana de Jesus (2018)
The current state of the world's energy resources has been contributing to the focus on research and testing that uses the energy present in lignocellulosic biomass to be converted into liquid, gaseous or solid fuels. The agricultural residues are distinguished by the quantity that are generated in agroindustrial countries like Brazil. In this work, the coffee husk was evaluated as agroindustrial residue to generate energy through the pyrolysis process, estimating the activation energy as the main kinetic parameter through thermogravimetric data. The coffee husk was characterized by means of immediate, elemental, lignocellulosic analysis, calorific value, X-ray fluorescence and infrared vibrational spectroscopy. The pyrolysis reaction was performed in order to analyze the operating conditions of the process, besides the characterization of the liquid product by GC / MS. It was determined by thermogravimetric analysis the most appropriate temperature range for pyrolysis of the coffee husk (673 - 773 K) and through the kinetic models, which described the pyrolysis reaction process satisfactorily, it was possible to determine the activation energy for the coffee husk (124.10 - 133.27 kJ / mol). The biomass was submitted by a thermal conversion process, more precisely conventional pyrolysis in fixed bed, for analysis of parameters such as temperature and average diameter, in which the influence of temperature in this process was highlighted. Through the characterization of the product of the liquid fraction obtained, it was possible to identify, in the majority, phenolic compounds and caffeine. The possibility of forming chemicals with diversified utilities and high added value makes pyrolysis one of the most promising thermal conversion technologies. The obtained heat value, 18.17 kJ / g, as well as results of elemental analysis and immediate analysis, show that this biomass has a potential for use as an energy source.